Dystrophic microglia in the aging human brain - Streit, Wolfgang J.; Sammons, Nicole W.; Kuhns, Amanda J.; Sparks, D. Larry (Glia, 2004)
We have studied microglial morphology in the human cerebral cortex of two nondemented subjects using high‐resolution LN‐3 immunohistochemistry. Several abnormalities in microglial cytoplasmic structure, including deramification, spheroid formation, gnarling, and fragmentation of processes, were identified. These changes were determined to be different from the morphological changes that occur during microglial activation and they were designated collectively as microglial dystrophy. Quantitative evaluation of dystrophic changes in microglia revealed that these were much more prevalent in the older subject (68‐year‐old) than in the younger one (38‐year‐old). Thus, we conclude that microglial dystrophy is a sign of microglial cell senescence. We hypothesize that microglial senescence could be important for understanding age‐related declines in cognitive function. © 2003 Wiley‐Liss, Inc.